The Effect of E-Service Quality and Brand Image Toward Netflix Customer Loyalty through Customer Satisfaction - Haura Kurniati; Agung Kresnamurti Rivai Prabumenang; Shandy Aditya (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2021)
This research aims to determine the effect of e-service quality and brand image on customer satisfaction and customer loyalty towards Netflix’s user. This research uses quantitative method and the data collection use survey method with questionnaires as the instrument. The sample of this research is 200 respondents who live in DKI Jakarta and have used Netflix in the past 6 months. Data were analyzed using software SPSS version 25 and SEM (Structural Equation Model) from Lisrel 8.8 to process and analyze the research data. The result of hypothesis testing shows that e-service quality has significant effect on customer satisfaction, but not on customer loyalty. However, e-service quality has significant effect on customer loyalty through customer satisfaction. The result also found that brand image has significant effect on both customer satisfaction and customer loyalty. And customer satisfaction has the most influence on customer loyalty.